Assessment of genetically modified oilseed rape MS8, RF3 and MS8×RF3 for renewal of authorisation under regulation (EC) No 1829/2003 (application EFSA‐GMO‐RX‐004). (28th November 2017) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: Following the submission of application EFSA‐GMO‐RX‐004 under Regulation (EC) No 1829/2003 from Bayer CropScience, the Panel on Genetically Modified Organisms of the European Food Safety Authority (GMO Panel) was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application of the genetically modified (GM) herbicide‐tolerant oilseed rape MS8, RF3 and MS8×RF3. The data received in the context of this renewal application contain post‐market environmental monitoring reports, systematic searches and evaluation of literature, updated bioinformatics analyses, and additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequence of the event in oilseed rape MS8, RF3 and MS8×RF3 considered for renewed authorisation is identical to the sequence of the originally assessed event, the GMO Panel concludes that there is no evidence in the context of this renewal application for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on oilseed rape MS8, RF3 and MS8×RF3.